2017
DOI: 10.1111/inr.12403
|View full text |Cite
|
Sign up to set email alerts
|

Public, patient and carers’ views on palliative and end‐of‐life care in India

Abstract: Nurses can be central in gathering the contextual evidence that advocate users' perspectives to inform further studies and national palliative care policies in India. Emerging policies in nursing education need to focus on integrating family-centred palliative and end-of-life care within curricula, whereas nursing practice may promote nurse-led community models to address the patchy palliative and end-of-life service provision in India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
1
9
0
1
Order By: Relevance
“…A review published in 2019 highlighted the lack of basic living amenities for terminally ill patients the inability of Indians to cope with the financial burdens of terminal illness and death. [ 24 ] They also found that most people prefer to die at home surrounded by family and patients tend to hide their emotions and suffering from their family and caregivers to not add to their burden of care. In a 2022 study done among cancer patients in six developing countries, including India, 35% of patients reported experiencing at least one facet of cancer-related stigma often, while 60% reported experiencing it occasionally; those who perceived stigma were less likely to opt for life-extending treatments.…”
Section: Issues With Palliative Care In Indiamentioning
confidence: 99%
“…A review published in 2019 highlighted the lack of basic living amenities for terminally ill patients the inability of Indians to cope with the financial burdens of terminal illness and death. [ 24 ] They also found that most people prefer to die at home surrounded by family and patients tend to hide their emotions and suffering from their family and caregivers to not add to their burden of care. In a 2022 study done among cancer patients in six developing countries, including India, 35% of patients reported experiencing at least one facet of cancer-related stigma often, while 60% reported experiencing it occasionally; those who perceived stigma were less likely to opt for life-extending treatments.…”
Section: Issues With Palliative Care In Indiamentioning
confidence: 99%
“…No caso de pacientes terminais a assistência de enfermagem deve explorar as necessidades físicas, espirituais, psicossociais do indivíduo, estando atenta a preferência do local da morte, a situação domiciliar do paciente e as necessidades informais dos familiares, como a utilização de mantras, água benta, amuletos, fotos de seu Deus; geralmente utilizados como forma de receber força em períodos de sofrimento (Venkatasalu et al, 2018).…”
Section: Condutas De Enfermagem Correlacionadas Com O Tratamento E/ou Terapia Cultural Religiosaunclassified
“…Data reduction techniques utilise the process of coding the data in order to 'simplify, abstract, focus and organise it into manageable features' (Ramasamy Venkatasalu et al, 2017). The study adopted subgrouping and single page tabulation as valid and reliable coding techniques in order to enhance methodological rigour (Broome, 2000, Brown et al, 2003.…”
Section: Data Reductionmentioning
confidence: 99%